2018
DOI: 10.1155/2018/5715819
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Performance of Zr‐Containing 354‐Type Al‐Si‐Cu‐Mg Cast Alloy: Role of Additions and Heat Treatment

Abstract: In this article, the volume fraction of intermetallic compounds in Zr-containing 354-type Al-Si-Cu-Mg alloys, characteristics of eutectic Si particles, and tensile, hardness, and impact properties have been evaluated with varying Ni and Mn contents and combination. The results revealed that additions of Ni and Mn in different amounts and combinations increased the volume fraction of intermetallic compounds in the tailored alloys, compared to the base alloy (cf. 12.21% for 4% Ni-containing alloy with 2.5% for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…e base alloy in this research work is 354-type alloy with a minor addition of Zirconium (Zr) (∼0.3 wt.%). is alloy was selected based on its improved room-and high-temperature tensile properties as reported in previous studies in the same research group [14,19]. e as-received 354 alloy ingots were cut, dried, and melted in a 70-Kg capacity SiC crucible using an electric resistance furnace.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…e base alloy in this research work is 354-type alloy with a minor addition of Zirconium (Zr) (∼0.3 wt.%). is alloy was selected based on its improved room-and high-temperature tensile properties as reported in previous studies in the same research group [14,19]. e as-received 354 alloy ingots were cut, dried, and melted in a 70-Kg capacity SiC crucible using an electric resistance furnace.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies [14][15][16][17][18][19][20][21][22] have been carried out in the past decade on how to maintain the mechanical properties of aluminum alloys at service temperatures that exceed 200°C. Among these, the addition of small amounts of transition metals was found to be a promising approach to maintain the mechanical properties of aluminum alloys at temperatures of up to 300°C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, efforts have been made for improving cast alloys mechanical properties, mainly in superior temperatures than the ones of the conventional applications. A significant number of studies on cast Al-Si-Cu-Mg alloys [13][14][15][16][17][18] were conducted due to its important applications in the transport sector in a large variety of components. Basically, in order to improve the strength, particularly at high temperatures, alloying elements that exhibit both limited solid solubility and low diffusivity in Al must be added [19].…”
Section: Introductionmentioning
confidence: 99%
“…Basically, in order to improve the strength, particularly at high temperatures, alloying elements that exhibit both limited solid solubility and low diffusivity in Al must be added [19]. Recent studies on aluminum alloys modified with the minor Zr additions [3,5,16,[20][21][22]] demonstrated a significant enhancement in high-temperature mechanical properties due to the increase of volume fraction of highstable intermetallic phases formed in the microstructure.…”
Section: Introductionmentioning
confidence: 99%